(untitled) (Research, Society and Development, 2020)
This work aims to describe the Mangalarga Marchador horse’s breeding systems in the Rio de Janeiro. The geographic distribution of the farms in the mesoregions of Rio de Janeiro State were defined, and the commercial and social importance the Mangalarga Marchador horse’s business is described in this study. Mangalarga Marchador horse breeders were interviewed through a survey. Sampling of the farms was stratified by the mesoregions. The state of Rio de Janeiro has 1,573 members Horse Breeder Association, with 92,162 registered horses, corresponding to 15.43% of the total of Mangalarga Marchador horses in Brazil. Approximately 95.2% of farms have their own area and more than half ranging between 100 to 500ha. Horse breeding is the main activity on 79.2% of the farms, and the main goal is the sale of horses (39%), followed by sports (32.7%) and leisure (18.6%). The properties have, on average, five registered employees. Most of the owners (90%) are male. The average number of horses at these farms is 100 heads, with an average number of 53 mares, maintained mainly on an extensive production system. About 39.9% of pastures are formed by the Brachiaria spp. grass, and Napier grass, also known as Elephant grass, the most used forage supplement. The average monthly consumption of forage and commercial concentrate feed is 12,866kg and 2,800kg respectively per farm. About 90% of breeders declared that the unskilled labor force is the biggest obstacle to the increase of the horse breeding in the Rio de Janeiro.